2019
DOI: 10.1002/nml.21352
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management, employee engagement, and nonprofit hospital performance

Abstract: Human resource management (HRM) has been shown to impact organizational performance, but more research is needed on particular human resource (HR) practices in nonprofits and their effect on performance. In this article, we explore one HRM practice argued to influence performance, employee engagement in decision‐making, examining whether involving staff at different levels of a nonprofit affects nonprofit organizational performance. Drawing on data from a 2011 study of nonprofit hospitals, we find employee eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 100 publications
0
24
0
1
Order By: Relevance
“…Increased perceptions of organization‐related social identity increase employees' affective commitment and consequently their willingness to perform (Marique et al, ; Raineri, ). A recent study by Johansen and Sowa () suggested that employee engagement in decision‐making (an aspect of inclusion; Mor Barak, ) may affect intermediate outcomes, such as satisfaction and commitment, which then in turn influence service and performance outcomes. Thus, it is possible that feelings of inclusion foster employee affective commitment which then increase work group performance.
Hypothesis 3: Climate for inclusion will be positively associated with perceptions of work group performance through increased affective commitment .
…”
Section: Literature and Conceptual Modelmentioning
confidence: 99%
“…Increased perceptions of organization‐related social identity increase employees' affective commitment and consequently their willingness to perform (Marique et al, ; Raineri, ). A recent study by Johansen and Sowa () suggested that employee engagement in decision‐making (an aspect of inclusion; Mor Barak, ) may affect intermediate outcomes, such as satisfaction and commitment, which then in turn influence service and performance outcomes. Thus, it is possible that feelings of inclusion foster employee affective commitment which then increase work group performance.
Hypothesis 3: Climate for inclusion will be positively associated with perceptions of work group performance through increased affective commitment .
…”
Section: Literature and Conceptual Modelmentioning
confidence: 99%
“…Furthermore, it is suggested that organizations should imbed engagement in human resource practices such as recruitment, performance management, socialization, and training and development as proposed in recent studies. The human resource practices directly influence employee engagement (Johansen & Sowa, 2019).…”
Section: Employee Engagement: An Overviewmentioning
confidence: 99%
“…Such leadership only transpires when followers invest their holistic selves into the performances of their role—the generally accepted definition of engagement (Rich et al, ). Engagement can also be considered a useful follower outcome as it is generative of job (Johansen & Sowa, ) and organizational (Rich et al, ) performances.…”
Section: Responding To Secondary Trauma In Nonprofit Human Service Ormentioning
confidence: 99%